2023
DOI: 10.1039/d3cc00962a
|View full text |Cite
|
Sign up to set email alerts
|

Organelle-targeted gene delivery in plants by nanomaterials

Abstract: This feature article highlights the latest developments and our strategies in organelle-specific nanomaterial delivery within plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…In a hybrid system based on C. pyrenoidosa , for instance, Au nanoparticles (AuNPs) are mineralized around the thylakoid membrane, augmenting the algae’s photosynthetic electron transport chain and enhancing light-driven hypoxic H 2 production . Various nanomaterials with organelle-targeting capabilities have been developed for subcellular delivery of genes or chemical cargos in plant cells. They have also found applications in imaging and therapeutic purposes for mammalian cells. , Conversely, mapping the subcellular distribution of nanomaterials lacking organelle-targeting properties also provides evidence for optimizing material-to-enzyme energy transport. This is achievable by engineering the target enzymes to express in subcellular locations or organelles where the nanomaterials are more abundant.…”
Section: Cross-membrane Energy Transportmentioning
confidence: 99%
“…In a hybrid system based on C. pyrenoidosa , for instance, Au nanoparticles (AuNPs) are mineralized around the thylakoid membrane, augmenting the algae’s photosynthetic electron transport chain and enhancing light-driven hypoxic H 2 production . Various nanomaterials with organelle-targeting capabilities have been developed for subcellular delivery of genes or chemical cargos in plant cells. They have also found applications in imaging and therapeutic purposes for mammalian cells. , Conversely, mapping the subcellular distribution of nanomaterials lacking organelle-targeting properties also provides evidence for optimizing material-to-enzyme energy transport. This is achievable by engineering the target enzymes to express in subcellular locations or organelles where the nanomaterials are more abundant.…”
Section: Cross-membrane Energy Transportmentioning
confidence: 99%
“…[ 9–11 ] The main challenge in delivering genetic materials by nanocarriers to plant cells is the penetration of the carrier through the cell wall, [ 12 ] which is generally accomplished by plasmodesmata, [ 13 ] endocytosis, [ 14 ] and/or physical disruption. [ 15 ] Recent studies have shown that carbon nanotubes, [ 9,11,16–20 ] mesoporous silica nanoparticles, [ 21,22 ] starch nanoparticles, [ 23 ] rosette nanotubes, [ 24 ] magnetic nanoparticles, [ 25 ] and nanosheets [ 26,27 ] can serve as efficient nanocarriers for DNA and RNA delivery to plant cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] These organelles participate in signaling pathways that drive malignant behavior including heightened metabolism [3,4] and anti-oxidative stress responses. [5,6] Current approaches, such as chemotherapy, [7][8][9] gene therapy, [10,11] and reactive oxygen species (ROS)-based therapies, [12][13][14][15] are commonly used to regulate cellular organelles due to their action sites within the organelles. However, the nonspecific diffusion of drugs can disrupt normal cellular ecology, necessitating the development of personalized strategies for the precise intracellular regulation of subcellular organelles.…”
Section: Introductionmentioning
confidence: 99%